Effects of Endurance Exercise Modalities on Arterial Stiffness in Patients Suffering from Unipolar Depression: A Randomized Controlled Trial - Hanssen, Henner; Minghetti, Alice; Faude, Oliver; Schmidt-Trucksäss, Arno; Zahner, Lukas; Beck, Johannes; Donath, Lars (Frontiers in Psychiatry, 2018)
Background: Psychiatric disorders are associated with a higher prevalence of cardiovascular disease (CVD) and mortality. Regular exercise has been shown to reduce depressive symptoms and improve arterial stiffness as a biomarker of cardiovascular risk. We aimed to investigate the effects of different exercise modalities on depression severity index and arterial stiffness in patients suffering from unipolar depression. Methods: 34 patients suffering from unipolar depression (female: 25, male: 9, age: 37.8, BDI-II score: 31.0) were enrolled in this two-armed randomized controlled trial. Central haemodynamics, augmentation index at heart rate 75/min (AIx@75) and aortic pulse wave velocity (PWV) were obtained by an oscillometric monitoring device. Maximal bicycle ergometer exercise testing yielded maximal fitness parameters. Patients were assigned to either high intensity low volume (HILV) or moderate continuous training (MCT). Both intervention groups trained three times a week during a four-week intervention period. Beck-Depression-Inventory-II (BDI-II) were filled out by the patients before and after the intervention period. Results: We found moderate interaction effects on depression severity reduction (ɳp²=0.10). With 85% likely beneficial effects, HILV was more effective in lowering BDI-II scores than MCT (HILV: pre: 28.8 (9.5), post: 15.5 (8.5), SMD=1.48), MCT: (pre: 33.8 (8.5), post: 22.6 (7.5), SMD=1.40). Reduction of AIx@75 was more pronounced after MCT (SMD=0.61) compared to HILV (SMD=0.08), showing 37% possibly beneficial effects of MCT over HILV. PWV remained unchanged in both training groups. Conclusion: Both training regimes showed large effects on the reduction of depressive symptoms. While HILV was more effective in lowering depression severity, MCT was more effective in additionally lowering peripheral arterial stiffness. Exercise should be considered an important strategy for preventive as well as rehabilitative treatment in depression.